Do not neglect surroundings in restoration of disturbed sites. Issue 3 (6th March 2015) - Prach, Karel; Karešová, Petra; Jírová, Alena; Dvořáková, Helena; Konvalinková, Petra; Řehounková, Klára
<x xml:space="preserve">Abstract</x> We examined the influence of surroundings, i.e. proximity effects, on the course of spontaneous vegetation succession using two data sets. In the first data set, we tested the effects of surrounding vegetation (woodlands, wetlands, grasslands, and synanthropic) on succession in various disturbed habitats in the Czech Republic by comparing successional sites with more natural vegetation within 100 m and at 1 km from each site. The habitats included old fields, gravel‐sand pits, spoil heaps from black coal mining, industrially extracted peatlands, and acidic stone quarries. We found that, with the exception of wetlands, the influence of the vegetation types on seral vegetation was nearly always significant using marginal and partial Canonical Correspondence Analyses. In the second data set, which included 27 limestone quarries, we compared species lists outside (up to 100 m apart) and inside the quarries using Detrended Correspondence Analysis and the Sørensen similarity index. We found much higher species similarity between outside and inside particular limestone quarries than among the quarries themselves and among their surroundings, which also indicates that the seral vegetation is decisively influenced by the surroundings. We argue that restoration ecologists should carefully consider the nature of the surroundings of disturbed sites because of its profound impact on restoration processes. They should conduct inventories and prescribe some restoration measures not only inside a restored site, but also in its surroundings.